The Indonesian Economy Trade and Industrial Policies - Ing, Lili Yan; Hanson, Gordon H.; Indrawati, Sri Mulyani (Routledge-ERIA Studies in Development Economics, 2018)
Against the backdrop of growing anti-globalisation sentiments and increasing fragmentation of the production process across countries, this book addresses how the Indonesian economy should respond and how Indonesia should shape its trade and industrial policies in this new world trade environment. The book introduces evaluation not on tariffs but on new trade instruments such as non-tariff measures (SPS, TBT, export measures and beyond border measures), and looks at industrial policies from a broader perspective such as investment, accessing inputs, labour, services, research and innovation policies. "The Open Access version of this book, available at http://www.taylorfrancis.com/books/10.4324/9781315161976, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license."